Quality of life of Nigerian stroke survivors and Its determinants (2015)
The disability caused by stroke could lead to significant decline in the level of functioning and deterioration of quality of life (QoL). QoL assessment could be used to evaluate the impact of stroke, assist in planning effective treatment, appraise efficacy of stroke rehabilitation, and evaluate cost effectiveness in order to justify expenditures on health care. This article reviewed the QoL of Nigerian stroke survivors and also identified its determinants. More than 70% of the studies on QoL of Nigerian stroke survivors have been conducted the in South Western part of Nigeria, and few from other parts of the country. The reported mean ages of stroke survivors in the published studies ranged between 54.40 years and 62.8 years. Stroke has moderate impact on QoL of Nigerian survivors, though they experienced lower QoL than their apparently healthy counterparts. The physical, social and emotional domains of QoL were all affected. Language and vision domains were however least affected. Stroke severity, disability and depression are the important predictors of QoL among Nigerian stroke survivors. The influence of motor recovery on QoL of Nigerian stroke survivors in the acute and sub-acute stages of recovery is subject to further research.